Strengthening capacity for pandemic preparedness among health care professionals through interdisciplinary online learning: a participatory mixed-methods evaluation - Maryirene Ibeto; Imtiaz Mahmood Tahir; Mukhtar Danmallam; Beatrice Kamau; Victor Mtaki; Paul Msanzya Zulu; Fred Tusabe; Helen Wangai; Chimwemwe Waya; Elizabeth Clery; Chizaram Fide-Nwaogu; Joanna Wild; et al. (Frontiers in Public Health, 2026)
Introduction Between January and March 2022, the UK Public Health Rapid Support Team delivered a master’s-level short course, Pandemics: Emergence, Spread and Response, designed to strengthen interdisciplinary knowledge and skills for pandemic preparedness. This study evaluated the course’s perceived usefulness, outcomes, and longer-term impacts on professional practice, one year after completion. Methods A participatory convergent mixed-methods design was used, involving course alumni as co-evaluators. Quantitative data were collected through an online survey (n = 31; 62% response rate), while qualitative data were generated through focus group discussions (FGDs), value creation stories (VCS), and iterative workshops. Wenger, Trayner and de Laat’s Value Creation Framework informed the evaluation design and interpretation of findings. Quantitative analyses were exploratory and intended to identify patterns rather than test formal hypothesis. Results Participants consistently reported that the course was relevant and useful to their professional roles. Exploratory analyses identified associations between perceived course usefulness and engagement, course content, delivery mode, learning platform, and facilitator diversity; these findings should be interpreted cautiously given the small sample size and exploratory design and should not be interpreted as causal. Qualitative findings provided explanatory depth by demonstrating how interactive pedagogy, interdisciplinary learning, practical case-based teaching, and exposure to diverse perspectives facilitated knowledge transfer and application in professional practice, generating value across Wenger’s cycles of immediate, potential, applied, realised and reframing value. Discussion Overall, the findings suggest that interdisciplinary, learner-centred online training may support professional practice change when engagement, inclusivity, and contextual relevance are prioritised. This study demonstrates the value of participatory, mixed-methods evaluation and Wenger’s Value Creation Framework for understanding long-term learning outcomes in pandemic preparedness training.